Estudio de la indumentaria del pueblo étnico Puruhá y la incidencia de la migración como factor transformación de la vestimenta tradicional - Colcha Velata, Mayra Elizabeth (2024)
This research project focuses on the study of the Puruhá people's clothing and the impact of migration as a factor of transformation in traditional dress. The main objective is to make visible the changes and transformations that show the female dress of the Cacha parish due to migration, which is the first Puruhá indigenous people who have managed to maintain their identity, customs and traditions active. To carry out this research. Different data collection strategies were implemented, such as interviews and observation sheets. One of the relevant findings is the transformation of the Puruhá women's traditional clothing; when people migrate, they acquire new ways of dressing, they follow fashion trends, therefore the clothing is transformed into a more modern one. In this sense, migration is a social problem that directly affects the transformation of clothing, both in form, design and materials. Regarding the use of clothing, older women are the ones who keep the native dress of the village. On the other hand, young women and adolescents only use it for special occasions, since for daily use they combine it with western garments or do not use it at all. Regarding indigenous fashion brands, it helps to motivate people who migrated to use the clothing, to recognize their roots again. On the other hand, some garments are being discontinued, giving way to more modern clothing. In addition, there are several garments that have been discontinued, such as the nightgown.